2012
DOI: 10.1017/s0265051711000386
|View full text |Cite
|
Sign up to set email alerts
|

Storying music and the arts education: the generalist teacher voice

Abstract: For students in Years 1–10 in Queensland, Australia, The Arts (hereafter referred to as ‘arts’) is one of eight Key Learning Areas in the core curriculum. Yet, while arts – comprising five strands including music – is a mandatory component of the curriculum, implementation varies widely. This occurs for a range of reasons, one of which is the common practice that generalist teachers are allocated delivery of the arts programme in their teaching load. Furthermore, research reveals that music and the arts are fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
2
15
0
3
Order By: Relevance
“…A study by Hocking (2009) pointed out that "New South Wales is the only state to clearly set a minimum requirement for creative arts training: 36 hours for a graduate degree and 72 hours for an undergraduate degree" (p. 4). This is consistent with other international studies which have shown that the Arts are often marginalised in teacher education programmes (Garvis & Pendergast, 2012;Nompula, 2013).…”
Section: The Arts/music Curriculum For Ite Programmessupporting
confidence: 92%
“…A study by Hocking (2009) pointed out that "New South Wales is the only state to clearly set a minimum requirement for creative arts training: 36 hours for a graduate degree and 72 hours for an undergraduate degree" (p. 4). This is consistent with other international studies which have shown that the Arts are often marginalised in teacher education programmes (Garvis & Pendergast, 2012;Nompula, 2013).…”
Section: The Arts/music Curriculum For Ite Programmessupporting
confidence: 92%
“…Despite the fact that novice teachers tend to believe that engagement in the arts is an important component of every child's education, novice teachers rarely integrate the arts into their curriculum and instruction (Oreck, 2004). In addition to novice teachers' insecurities, the current era of accountability in schools provides an additional pressure that may make novice teachers reluctant to engage in curricular innovation, including innovation that attempts to integrate the arts with "high-stakes" content (Donahue & Stuart, 2008;Garvis & Pendergast, 2012;Mishook & Kornhaber, 2006;Oreck, 2004;Wexler, 2014). STEAM education requires authentic engagement in the arts; and, yet, most novice teachers report using arts-integrated lessons as a way to make the classroom more engaging and enjoyable (Donahue & Stuart, 2008;Oreck, 2004).…”
Section: Challenges Related To Teaching With Arts-integrationmentioning
confidence: 99%
“…Teachers' stories provide accessible and engaging opportunities to gain knowledge of teachers and schools (Garvis & Pendergast, 2012;Preskill, 1998). By considering and engaging with teachers' stories, other teachers can gain understanding, broaden vision, increase interpretive competence, and enrich practical repertoires (Conle, 2003).…”
Section: Introductionmentioning
confidence: 99%